Fear of an HIV positive test result: an exploration of the low uptake of couples HIV counselling and testing (CHCT) in a rural setting in Mukono district, Uganda. (December 2017) - Nannozi, Victoria; Wobudeya, Eric; Gahagan, Jacqueline
Background: Couples HIV counselling and testing (CHCT) is a key preventive strategy used to reduce the spread of HIV. In Uganda, HIV prevalence among married or cohabiting couples is 5.6%, compared to 2.2% among those never married. CHCT can help ease disclosure of HIV positive status, which in turn may help increase opportunities to obtain social supports and reduce new infections. The purpose of this study was aimed at exploring the possible reasons for the low uptake of CHCT in Mukono district, a rural in setting in Uganda. Methods: The study was conducted in two sub-counties in a rural district (Mukono district) using a descriptive qualitative research design. Specifically, we conducted four focus group discussions and 10 key informant interviews. We also interviewed 53 individuals in couple relationships. Data were collected mainly in the local language Luganda and English, all data were transcribed into English and coded for emergent themes. Ethical clearance for this study was obtained from the Mengo Hospital Research Review Board and from the Uganda National Council of Science and Technology. Results: Fear of a positive HIV test result emerged strongly as the most significant barrier to CHCT. To a lesser extent, perceptions and knowledge of CHCT, mistrust in marriages and culture were also noted by participants as important barriers to the uptake of CHCT among couples. Participants offered suggestions on ways to overcome these barriers, including peer couple counselling, offering incentives to couples that test together and door-to-door CHCT testing. Conclusion: In an effort to improve the uptake of CHCT, it is crucial to involve both females and males in the planning and implementation of CHCT, as well as to address the misconceptions about CHCT and to prioritise CHCT within health care systems management.